Implementation of a quality management system according to ISo 9001:2015 standards in an Angiology Unit: an Italian experience - Avruscio, G.; Ragazzo, S.; Ceccato, D.; Adamo, A.; Napoli, C.; Cacco, L.; Scalzotto, F.; Canciani, M.; Cognolato, M.; Fedele, A.; Scipioni, A.; Tocco Tussardi, I. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The International Standardization Organization operates the world’s most widely recognized quality management system standard, the ISO 9001:2015. In the healthcare sector, the adoption of this standard within an organization helps to improve the overall performance and provides a foundation for development and continuous progress. Our study aims to describe the implementation process of a quality management system according to the ISO 9001:2015 standards in an Angiology Unit of an Italian University hospital. Methods. The project was structured in 5 operational phases, which were carried out during a time frame of 14 months (March 2018-May 2019) and entailed several improvement actions associated with quality and safety outputs such as clinical management, clinical practice, safety, and patient-centeredness. Results. Implementation of the quality management system led to the improvement of many aspects of the processes performed in the Angiology Unit, both in the outpatient and day hospital setting. Overall, the project positively impacted on systems for patient safety, particularly in communication and data transmission, and clinical leadership.Conclusions. The implementation of the ISO 9001 certification is a process that apparently may seem expensive in terms of resources used, commitment, work, comparison, but it leads to substantial and always progressive improvements in the offer of Services to the user, safety both for the users and for the healthcare personnel involved, in addition to the care processes that translate into significant benefits in terms of quality of care for patients, as well as management savings for the organization.